STUDI PERBANDINGAN MINAT BELAJAR MAHASISWA PENERIMA BEASISWA DAN BUKAN PENERIMA BEASISWA DI PRODI PPKN FKIP UNIVERITAS RIAU - Naylil Rahmi Autari; Gimin, Gimin; Hambali, Hambali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the fact that education has a very important role in the progress of a nation, but there are still several problems for society in getting access to education, one of which is the cost factor. Therefore, the government provides various conveniences for underprivileged people who want to continue their education. through a scholarship program. Scholarships are given with several requirements, one of which is study achievement, thus students who apply for scholarships are required to maintain their study achievements during the study process so that the scholarship program is not revoked, meanwhile, in order for study achievements to continue to increase, students must also continue to maintain and increase their interest in learning. This research aims to determine the differences in language learning interests of scholarship recipients and non-scholarship recipients in the Pancasila and Citizenship Education Study Program, Faculty of Teacher Training and Education, Riau University. The type of research that will be carried out by the author is descriptive quantitative. The research was conducted at the Pancasila and Citizenship Education Study Program, Faculty of Teacher Training and Education, Riau University. The population in the study were all students of the Pancasila and Citizenship Education Study Program, Faculty of Teacher Training and Education, Riau University, class 2019 to 2021. The research sampling technique used was purposive sampling, the number of samples was 146 people. Data collection techniques were carried out using observation, interviews and questionnaires. The data analysis technique was carried out using the independent sample t-test statistical test. The results of data analysis show that there is a mean difference of 1.9589 with the sig value. 0.009 <0.05 so it can be concluded that there is a difference in the learning interest of scholarship recipients and non-recipient students in the Pancasila and Citizenship Education Study Program, Faculty of Teacher Training and Education, Riau University.